Adaptive reuse of port heritage leads to urban waterfront regeneration: a aproposed case study in Zhuzhou City, China - Asmawan Mohd Sarman,; Mohamad Ibrahim Mohamad,; Guo, Min Wei; Shen, Ling; Jiang, Mian (Penerbit Universiti Kebangsaan Malaysia, 2023)
Improvements in transportation and logistics have forced many ports lost their functional status even abandoned in the recent globalization context. While these deteriorated port-related area could get revitalization when reusing the port heritage as a catalyst to rebuild the better connection to the city, just as the ideal redevelopment projects worldwide have revealed. They provide ways to identify and conserve the port heritage, especially set a research foundation to explore how to use them for urban economic, social-cultural and environmental sustainability. In this sense, three common perspectives towards adaptive reuse of the port heritage have been introduced, respectively representing as multi-functional creator, adhesive back to the city and environmental-friendly messenger, based on which, practical implementation can be directly performed despite the scale of the port area. Consequently, this approach selects a typical port heritage site (Yong Li dockyard) in Zhuzhou, which is just an average industrial port city in center China, to illustrate that the essential factors extracted from project icons will also work for proceedings with considering their own context. In addition, a visual adaptive reuse plan is proposed, aiming to trigger the urban waterfront regeneration by recreating the port heritage as new roles to increase economy, satisfy residents and improve environment. Additionally, this research might shed lights on other cities with potentials.